PENGARUH PELVIC ROCKING EXERCISE TERHADAP PENGURANGAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI PMB “E” WILAYAH KERJA PUSKESMAS BULULAWANG KABUPATEN MALANG: Effect Of Pelvic Rocking Exercise On Pain Reduction Background On Trimester III Pregnant Women In Pmb “E” Working Area Of Bululawang Puskesmas, Malang District - Anggrawati Wulandari (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2021)
ABSTRACT Women who have had back pain before pregnancy are at higher risk of experiencing the same thing when pregnant. Therefore, it is very important to be able to differentiate pregnancy back pain from back pain that occurs due to other causes. The purpose of this study was to analyze the effect of Pelvic Rocking exercise on the reduction of back pain in trimester III pregnant women in the Bululawang Community Health Center, Malang Regency. This research design uses correlational analytic with one group pre test design approach. The population in this study were all pregnant women in PMB "E" working area of ??Puskesmas Bululawang 73 pregnant women with a sample size of 30 respondents who were taken using accidental sampling technique. The independent variable in this study was Pelvic Rocking exercise, while the dependent variable was back pain for pregnant women. Data analysis used the Wilcoxson test. Results of the Research Before giving treatment, the highest level of back pain was moderate pain as much as 18 pregnant women (60%), and after giving Pelvic Rocking exercise, the pain level was reduced by 26 pregnant women (86.7%). The Wilcoxson test results show that the p value or 0.002 <0.005, then Ho is rejected, thus the alternative hypothesis (H1) is accepted. So the conclusion is that there is a significant effect between Pelvic Rocking Exercise on the reduction of back pain in trimester III pregnant women at PMB "E" in the working area of ??the Bululawang Community Health Center. The conclusion of this study is that there is an effect of Pelvic Rocking Exercise on the reduction of back pain in trimester III pregnant women at PMB "E" in the working area of ??Bululawang Public Health Center.   Keywords : Pelvic Rocking exercise, Back pain, pregnant women